The Effectiveness of Obstacle Race Game toward Students’ Motivation in Learning Grammar - Baiq Deni Kurniati (Journal of Languages and Language Teaching, 2018)
This research was aimed to find out the effectiveness of Obstacle Race Game toward students’ motivation in learning grammar and to find out the correlation between students’ motivation and grammar at MA Darul Husaini Sanggeng. The kind of this research is experimental research (quantitative approach). This research design was applied pretest-posttest design. The population of this research was all of the second grade students of MA Darul Husaini Sanggeng. The sample of this research was consist of two classes namely XI-A as experimental class consist of 17 students and XI-B as control class consist of 17 students. The sample technique used in this research was saturated sampling technique. The technique which was used to analysis the data was t-test and r-test formula. From the research data found that the t-test score is higher than t-table (2,635>2, 021). Based on the result of this research, it can be conclude that the Obstacle Race Game has positive effect towards students’ motivation in learning grammar. From the research data found that r-test is higher than r-table (0,990>0,482). It can be conclude that there is correlation between students’ motivation and grammar.